Pravna ureditev varstva potrošnikov: Učinkovito uveljavljanje pravic v luči ciljev krožnega gospodarstva (University of Maribor Press, 2022)
Legal Regulation of Consumer Protection: Effective Enforcement of Rights in the Light of Circular Economy Goals. As part of the Student Innovative Project for Social Benefit (ŠIPK) 2016-2020 PUPKRO, the students intensively studied the intertwining of two goals pursued in the EU (and thus of course also in Slovenia): a high level of environmental protection and a high level of consumer protection. These two goals are often in conflict, and it is us as consumers who, by changing our habits, can significantly contribute to a faster transition from a linear to a circular economy. Together with the cooperation of a non-economic partner, the PIP Institute, and eight students from four faculties of the University of Maribor, the project and the present monograph focused on the legal, behavioral, economic and engineering dilemmas of the circular economy. The purpose of the publication is to raise the awareness of the general public of consumer rights within the circular economy process and to prepare guidelines for more effective enforcement of these rights in practice. In addition to making consumers aware of their rights, the goal is also to empower them for a green transition and thereby take care of environmental protection.